Analysis of the Implementation of Character Education at SMP PGRI Kasihan - Najamudin Dano Syaifuddin; Muhammad Wasith Achadi (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study discusses the implementation of character education at SMP PGRI Kasihan which faces the challenge of moral degradation among adolescents. The purpose of this study is to analyze the application of religious habits and school culture in shaping students' disciplinary character and manners. The method used is a descriptive qualitative approach with in-depth interview, observation, and documentation techniques. The results of the study show that the activities of tadarus Al-Qur'an and the 5S culture (Smile, Greeting, Greeting, Polite, Polite) consistently shape students' religious behavior, discipline, and responsibility. Teachers play an important role as role models and fosters of moral values. In conclusion, character education based on religious habituation is effective in fostering students' moral and social values. It is recommended that schools expand habituation programs and increase digital literacy-based character strengthening training.